PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN KANTOR PUSAT PT KIMIA FARMA - Jamaludin Khalid; Ria Maryati (Human Capital Development, 2019)
Purpose- This study aims to discuss the Cultural Organization, Compensation and Team Cooperation for Employee Performance. The basic concept of Equity Respondents was taken from 100 employees of THE Head office of PT Kimia Farma. Design/methology/approach - The sampling technique uses the roscue sampling technique. Data analysis techniques used multiple linear regression analysis. Findings- The results of the analysis can conclude that the Cultural Organization, Compensation and Team Cooperation are positive and significant both simultaneously and partially on Work Performance. For organizational culture in the pharmacy chemistry it was approved at 4.248%, compensation 5.704% and team cooperatives at 7.391%. Simultaneously it was found that there was a change of variables altogether together to determine the performance of employees at Kimia Farma Pusat with a contribution of 41.603% where other factors involved but not approved in this study were only dominant at 58.39%. For this reason, Kimia Farma Management must maintain and increase the influence of organizational culture, compensation and opposing teamwork to improve performance so that chemical farma employees work better.